2016
DOI: 10.2147/ott.s114492
|View full text |Cite
|
Sign up to set email alerts
|

SPARC is a possible predictive marker for albumin-bound paclitaxel in non-small-cell lung cancer

Abstract: ObjectivesNanoparticle albumin-bound paclitaxel (nab-paclitaxel) produced good tumor response in cases with lung squamous cell carcinoma, one of the most difficult cancers to treat. Secreted protein acidic and rich in cysteine (SPARC) binds to albumin, suggesting that SPARC plays an important role in tumor uptake of nab-paclitaxel. There is as yet no predictive marker for cytotoxic agents against non-small-cell lung cancer (NSCLC), and hence we believed that SPARC expression might be associated with tumor resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 23 publications
(26 reference statements)
0
37
0
Order By: Relevance
“…Whether SPARC expression was a predictive biomarker to Nab-PTX therapy remains controversial. Some literatures [ 36 , 37 ] found that high stromal SPARC expression in the primary tumor might be a biomarker for Nab-PTX treatment of inferior PFS and OS in advanced pancreatic ductal adenocarcinoma and better survival in NSCLC. However, another study reported that SPARC expression did not seem to be associated with the efficacy of Nab-PTX in metastatic breast cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether SPARC expression was a predictive biomarker to Nab-PTX therapy remains controversial. Some literatures [ 36 , 37 ] found that high stromal SPARC expression in the primary tumor might be a biomarker for Nab-PTX treatment of inferior PFS and OS in advanced pancreatic ductal adenocarcinoma and better survival in NSCLC. However, another study reported that SPARC expression did not seem to be associated with the efficacy of Nab-PTX in metastatic breast cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nab-paclitaxel is a new paclitaxel and its tolerability, bioavailability and efficacy have been improved compared to standard paclitaxel (10). Nanoparticles of albuminpaclitaxel are absorbed by tumor cells from which paclitaxel is subsequently released to kill tumor cells (11). Compared with standard paclitaxel, nab-paclitaxel has an average particle size of 130 nm with minimal risk of capillary blockage (12) and enhances delivery of the cytotoxic agent to cancer cells.…”
Section: Figure 2 Overall Survival (Os) Of 34 Patients Who Received mentioning
confidence: 99%
“…In this case, the patient had a remarkable response with only 28 days of administration. Of note, in a recent study, the overexpression of secreted protein acidic and rich in cysteine (SPARC), which binds to albumin, was used as marker of treatment efficiency with afatinib 22. The patient did not have any adverse effects from the afatinib 40 mg administration.…”
Section: Discussionmentioning
confidence: 96%